Novel Insight Into Nutritional Regulation in Enhancement of Immune Status and Mediation of Inflammation Dynamics Integrated Study In Vivo and In Vitro of Teleost Grass Carp (Ctenopharyngodon idella): Administration of Threonine - Dong, Yu-Wen; Jiang, Wei-Dan; Wu, Pei; Liu, Yang; Kuang, Sheng-Yao; Tang, Ling; Tang, Wu-Neng; Zhou, Xiao-Qiu; Feng, Lin (Frontiers in Immunology, 2022)
This study aims to investigate the effects of threonine (Thr) on immunoregulation in vivo and in vitro of teleost grass carp (Ctenopharyngodon idella). Juveniles (9.53 ± 0.02 g) were reared for 8 weeks with respective Thr diet (3.99, 7.70, 10.72, 14.10, 17.96, and 21.66 g/kg) and then challenged with Aeromonas hydrophila for in vivo study. Macrophages isolated from head kidney were treated in vitro for 48 h with L-Thr (0, 0.5, 1.0, 2.0, 4.0, and 8.0 mM) after 6 h of lipopolysaccharide induction. The results showed that, compared with Thr deficiency (3.99 g/kg), the optimal dietary Thr (14.10g/kg) affected the immunocyte activation in the head kidney (HK) and spleen (SP) by downregulating the mRNA expressions of MHC-II and upregulating CD4 (not CD8), and it mediated the innate immune by enhancing the activities of lysozyme (LZ), acid phosphatase content of complement 3 (C3) and C4, increasing the mRNA abundances of hepcidin, liver expressed antimicrobial peptide-2A (LEAP-2A), LEAP-2B, β-defensin1, downregulating tumor necrosis factor α (TNF-α), IL-6, IL-1β, IL-12p35, IL-12p40, IL-17AF1, and IL-17D partly by attenuating RORγ1 transcriptional factor and nuclear factor kappa B p65 (NF-κBp65) signaling cascades [IKKβ/IκBα/NF-κBp65] and upregulating transforming growth factor β1 (TGF-β1), IL-4/13A, -4/13B, IL-10, and IL-22 partly by GATA-3. Besides these, the optimal dietary Thr regulated the adaptive immune by upregulating the mRNAs of immunoglobulin M (IgM) and IgZ (not IgD). Moreover, 2 mM Thr downregulated in vitro the mRNA abundances of colony stimulating factor-1, inducible nitric oxide synthase, mannose receptor 1, matrix metalloproteinase2 (MMP-2), and MMP-9 significantly (P < 0.05), indicating that Thr could attenuate the M1-type macrophages’ activation. Moreover, L-Thr downregulated the mRNA transcripts of TNF-α, IL-6, and IL-1β associated with impairing the SOCS1/STAT1 signaling and upregulated IL-10 and TGF-β1 partly by accentuating the SOCS3/STAT3 pathway. The above-mentioned observations suggested that Thr improved the immune status in the immune organs of fish by enhancing the immune defense and mediating the inflammation process. Finally, based on the immune indices of LZ activity in HK and C3 content in SP, the optimal Thr for immune enhancement in juvenile grass carp (9.53–53.43 g) was determined to be 15.70 g/kg diet (4.85 g/100 g protein) and 14.49 g/kg diet (4.47 g/100 g protein), respectively.